Global perspectives for the conservation and management of open-air rock art sites
1 online resource
Keywords: "Global Perspectives for the Conservation and Management of Open-Air Rock Art Sites responds to the growth in know rock art sites across the globe and addresses the need to investigate natural and human-originated threats to them as well as propose solutions to mitigate resulting deterioration. Bringing together perspectives of international research teams from across five continents, the chapters in this book are divided into four discrete parts that best reflect the worldwide scenarios where conservation and management of open-air rock art sites unfolds: 1) ethics, community and collaborative approaches; 2) methodological tools to support assessment and monitoring; 3) scientific examination and interventions; and 4) global community and collaborative case studies innovating methodologies for ongoing monitoring and management. The diverse origin of contributions results in a holistic and interdisciplinary approach that conciliates perceived intervention necessity, community and stakeholders' interests, and rigorous scientific analysis regarding open-air rock-art conservation and management. The book unites the voices of the global community in tackling a significant challenge: to ensure a better future for open-air rock art. Moving conservation and management of open-air rock art sites in from the periphery of conservation science, this volume is an indispensable guide for archaeologist, conservators and heritage professionals involved in rock art and its preservation"--